Identification and Characterization of Plant Vegetation in the Very Acid Environment of Kawah Putih Bandung - Anik Nafisah Maulida; Muhamad Jalil (JRST (Jurnal Riset Sains dan Teknologi), 2025)
Kawah Putih in Bandung Regency is an extreme environment with volcanic characteristics such as fluctuating temperatures, low soil pH and high sulfur levels. This research aims to identify and characterize plants in the region, as well as assess their morphological and physiological adaptations to extreme conditions. The field survey method in June 2024 recorded plant species and their characteristics. Some of the identified species include Vaccinium varingifolium (Cantigi), Polypodium feei (Tangkur Fern), Histiopteris incisa (Batwing Fern), and Litsea cubeba (Lemo). These plants show special adaptations: Vaccinium varingifolium has the ability to adapt to drought and high temperatures, Polypodium feei and Histiopteris incisa are able to overcome nutritional deficiencies and exposure to sulfur, while Litsea cubeba with its deep root adaptations can detoxify the environment. This research provides insight into plant adaptation strategies in extreme environments and the importance of conservation to protect local biodiversity and the economic potential of these plants.